The Burden of Smoking in the Health-Disease Process in People with Human Immunodeficiency Virus and AIDS - Yoenny Peña García; Luis Carlos Andraín Silva; Idalmis Sartorio Zayas; Dolys Suárez Padilla; Ana Julia Lozada Pérez (Universidad de las Ciencias Médicas de Cienfuegos, 2017)
Foundation: smoking affects individual, familial and social health of people living with the human immunodeficiency virus and AIDS. The effects of the habit on these patients influence morbidity and mortality and increase the risk of various diseases and affect the immune response to antiretroviral treatment. Objective: to determine the burden of smoking on the disease health process in patients living with human immunodeficiency virus and AIDS. Methods: an analytical cohort study was performed. It was analyzed as a dependent variable for smoking in people living with the human immunodeficiency virus and AIDS, and as independent variables: age, years of exposure (as a smoker), diseases that have suffered in the last 5 years, immunological condition, and response to antiretroviral therapy. The relative risk and the etiologic risk fraction were calculated, as well as the Chi2 test to estimate the strength of association between the independent and dependent variables. Results: smoking in patients living with human immunodeficiency virus and AIDS had a significant statistical association with different related effects, which in order of strength of association increases the risk of deterioration of the immune system and the incidence of malignant tumours and pneumonia Pneumocystis jirovecii. Conclusion: there was a causal relationship between smoking and the immunodeficiency virus in addition to the incidence of Pneumocystis jirovecii pneumonia. It was show that smoking impairs the immune condition of these patients and affects the adequate response to antiretroviral treatment.